Supportive-Educative Health Counseling in Dealing With Menarche in Elementary School Students: Penyuluhan Kesehatan Supportif-Edukatif Dalam Menghadapi Menarche Pada Siswi Sekolah Dasar - Sari Harahap, Asrika; Dynaria Siregar, Yetti; Noviyanti Harahap, Rizky; Nugraeny, Lolita; Ulpa Ismail, Ilvira; Hasma Marbun, Aghsila; Handayani, Purnama (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Adolescence is a time of physical and psychological changes which is usually called puberty. Puberty in adolescent girls is marked by the arrival of menarche, menarche is the first period of menstrual blood in women, usually occurs at the age of 10-16 years, while normal menarche occurs at the age of 12-13 years and currently the age of menarche is increasingly advanced, namely 10-16 years, this happens because it is influenced by nutritional status, heredity, socio-economics and exposure to mass media. The purpose of this research is to prepare yourself to face the arrival of menarche so you don't need to be afraid and worried. The respondents in this community service activity were 41 female students in class V & VI of SD IT Ar-Rayhan, Medan Amplas District. The method used was conducting a pretest by giving a questionnaire about menarche, then providing health education about menarche using tools, namely leaflets and posters, finally a posttest was carried out as an evaluation of female students' knowledge about menarche. The results of the study showed that respondents' knowledge was better after being given counseling about menarche compared to before being given the counseling. The knowledge category was good before the counseling was 26.8%, while after the counseling it increased to 87.8%. Therefore, significant differences were found in knowledge before and after being given counseling about menarche. Health education about menarche really helps female students to prepare themselves for the arrival of menarche so that female students no longer need to be afraid and afraid of menarche.